Phylogenetic structure and ancestry of Korean clawed salamander, Onychodactylus koreanus (Caudata: Hynobiidae). (19th May 2018) - Suk, Ho Young; Lee, Mu-Yeong; Bae, Han-Gyu; Lee, Seo-Jin; Poyarkov, Nikolay; Lee, Hang; Min, Mi-Sook
Abstract: Onychodactylus koreanus, a hynobiid salamander species endemic to the Korean Peninsula, can be regarded as a strict ecological specialist, probably vulnerable to anthropogenic environmental modifications and climate change. We used mitochondrial cytochrome b gene to analyze the genetic diversity and phylogenetic structure of O. koreanus from 19 populations collected in an attempt to cover its major distribution within South Korea. A total of 76 haplotypes of O. koreanus obtained in our analyses could be subdivided into three phylogenetic clades, KR, NE and SE. Clade KR haplotypes occur in most of the regions throughout the Korean Peninsula with four distinct subclades (KR I–IV). Clade NE and SE haplotypes were only observed in two populations YY and YS, respectively. Haplotype sharing was scarce even among populations in geographical proximity, and most of the populations were represented by a single clade or subclade, indicating the low level of gene flow among populations. O. koreanus likely originated from the historical southward dispersal of its ancestral lineages following divergence from Chinese O. zhaoermii that was recovered as the sister of O. koreanus in our phylogenetic analysis. Our results have critical implications for the taxonomic status of O. koreanus and its long-term management plan.